13 KiB
layout | title | date | permalink | categories | math |
---|---|---|---|---|---|
post | Typoclassopedia: Exercise solutions | 2017-09-27 | typoclassopedia-exercise-solutions/ | programming | true |
I wanted to get proficient in Haskell so I decided to follow An [Essential] Haskell Reading List, there I stumbled upon Typoclassopedia, while the material is great, I couldn't find solutions for the exercises to check against, so I decided I would write my own and hopefully the solutions would get fixed in case I have gone wrong by others. So if you think a solution is wrong, let me know in the comments!
In each section below, I left some reference material for the exercises and then the solutions.
Functor
Instances
instance Functor [] where
fmap :: (a -> b) -> [a] -> [b]
fmap _ [] = []
fmap g (x:xs) = g x : fmap g xs
-- or we could just say fmap = map
instance Functor Maybe where
fmap :: (a -> b) -> Maybe a -> Maybe b
fmap _ Nothing = Nothing
fmap g (Just a) = Just (g a)
((,) e) represents a container which holds an “annotation” of type e along with the actual value it holds. It might be clearer to write it as (e,), by analogy with an operator section like (1+), but that syntax is not allowed in types (although it is allowed in expressions with the TupleSections extension enabled). However, you can certainly think of it as (e,).
((->) e) (which can be thought of as (e ->); see above), the type of functions which take a value of type e as a parameter, is a Functor. As a container, (e -> a) represents a (possibly infinite) set of values of a, indexed by values of e. Alternatively, and more usefully, ((->) e) can be thought of as a context in which a value of type e is available to be consulted in a read-only fashion. This is also why ((->) e) is sometimes referred to as the reader monad; more on this later.
Exercises
-
Implement
Functor
instances forEither e
and((->) e)
.Solution:
instance Functor (Either e) where fmap _ (Left e) = Left e fmap g (Right a) = Right (g a) instance Functor ((->) e) where fmap g f = g . f
-
Implement
Functor
instances for((,) e)
and forPair
, defined as below. Explain their similarities and differences.Solution:
instance Functor ((,) e) where fmap g (a, b) = (a, g b) data Pair a = Pair a a instance Functor Pair where fmap g (Pair a b) = Pair (g a) (g b)
Their similarity is in the fact that they both represent types of two values. Their difference is that
((,) e)
(tuples of two) can have values of different types (kind of(,)
is* -> *
) while both values ofPair
have the same typea
, soPair
has kind*
. -
Implement a
Functor
instance for the typeITree
, defined asdata ITree a = Leaf (Int -> a) | Node [ITree a]
Solution:
instance Functor ITree where fmap g (Leaf f) = Leaf (g . f) fmap g (Node xs) = Node (fmap (fmap g) xs)
To test this instance, I defined a function to apply the tree to an
Int
:applyTree :: ITree a -> Int -> [a] applyTree (Leaf g) i = [g i] applyTree (Node []) _ = [] applyTree (Node (x:xs)) i = applyTree x i ++ applyTree (Node xs) i
This is not a standard tree traversing algorithm, I just wanted it to be simple for testing.
Now test the instance:
λ: let t = Node [Node [Leaf (+5), Leaf (+1)], Leaf (*2)] λ: applyTree t 1 [6,2,2] λ: applyTree (fmap id t) 1 [6,2,2] λ: applyTree (fmap (+10) t) 1 [16, 12, 12]
-
Give an example of a type of kind
* -> *
which cannot be made an instance ofFunctor
(without usingundefined
).I don't know the answer to this one yet!
-
Is this statement true or false?
The composition of two
Functor
s is also aFunctor
.If false, give a counterexample; if true, prove it by exhibiting some appropriate Haskell code.
Solution:
It's true, and can be proved by the following function:
ffmap :: (Functor f, Functor j) => (a -> b) -> f (j a) -> f (j b) ffmap g = fmap (fmap g)
You can test this on arbitrary compositions of
Functor
s:main = do let result :: Maybe (Either String Int) = ffmap (+ 2) (Just . Right $ 5) print result -- (Just (Right 7))
Functor Laws
fmap id = id
fmap (g . h) = (fmap g) . (fmap h)
Exercises
-
Although it is not possible for a Functor instance to satisfy the first Functor law but not the second (excluding undefined), the reverse is possible. Give an example of a (bogus) Functor instance which satisfies the second law but not the first.
Solution:
This is easy, consider this instance:
instance Functor [] where fmap _ [] = [1] fmap g (x:xs) = g x: fmap g xs
Then, you can test the first and second laws:
λ: fmap id [] -- [1], breaks the first law λ: fmap ((+1) . (+2)) [1,2] -- [4, 5], second law holds λ: fmap (+1) . fmap (+2) $ [1,2] -- [4, 5]
-
Which laws are violated by the evil Functor instance for list shown above: both laws, or the first law alone? Give specific counterexamples.
-- Evil Functor instance instance Functor [] where fmap :: (a -> b) -> [a] -> [b] fmap _ [] = [] fmap g (x:xs) = g x : g x : fmap g xs
Solution:
The instance defined breaks the first law (
fmap id [1] -- [1,1]
), but holds for the second law.
Category Theory
The Functor section links to Category Theory, so here I'm going to cover the exercises of that page, too.
Introduction to categories
Category laws:
-
The compositions of morphisms need to be associative:
f \circ (g \circ h) = (f \circ g) \circ h
-
The category needs to be closed under the composition operator. So if
f : B \to C
andg: A \to B
, then there must be someh: A \to C
in the category such thath = f \circ g
. -
Every object
A
in a category must have an identity morphism,id_A : A \to A
that is an identity of composition with other morphisms. So for every morphismg: A \to B
:g \circ id_A = id_B \circ g = g
.
Exercises
-
As was mentioned, any partial order
(P, \leq)
is a category with objects as the elements of P and a morphism between elements a and b iffa \leq b
. Which of the above laws guarantees the transitivity of\leq
?Solution:
The second law, which states that the category needs to be closed under the composition operator guarantess that because we have a morphism
a \leq b
, and another morphismb \leq c
, there must also be some other morphism such thata \leq c
. -
If we add another morphism to the above example, as illustrated below, it fails to be a category. Why? Hint: think about associativity of the composition operation.
Solution:
The first law does not hold:
f \circ (g \circ h) = (f \circ g) \circ h
To see that, we can evaluate each side to get an inequality:
g \circ h = id_B
f \circ g = id_A
f \circ (g \circ h) = f \circ id_B = f
(f \circ g) \circ h = id_A \circ h = h
f \neq h
Functors
Functor laws:
-
Given an identity morphism
id_A
on an objectA
,F(id_A)
must be the identity morphism onF(A)
, so:F(id_A) = id_{F(A)}
-
Functors must distribute over morphism composition:
F(f \circ g) = F(f) \circ F(g)
Exercises
-
Check the functor laws for the diagram below.
Solution:
The first law is obvious as it's directly written, the pale blue dotted arrows from
id_C
toF(id_C) = id_{F(C)}
andid_A
andid_B
toF(id_A) = F(id_B) = id_{F(A)} = id_{F(B)}
show this.The second law also holds, the only compositions in category
C
are betweenf
and identities, andg
and identities, there is no composition betweenf
andg
.(Note: The second law always hold as long as the first one does, as was seen in Typoclassopedia)
-
Check the laws for the Maybe and List functors.
Solution:
instance Functor [] where fmap :: (a -> b) -> [a] -> [b] fmap _ [] = [] fmap g (x:xs) = g x : fmap g xs -- check the first law for each part: fmap id [] = [] fmap id (x:xs) = id x : fmap id xs = x : fmap id xs -- the first law holds recursively -- check the second law for each part: fmap (f . g) [] = [] fmap (f . g) (x:xs) = (f . g) x : fmap (f . g) xs = f (g x) : fmap (f . g) xs fmap f (fmap g (x:xs)) = fmap f (g x : fmap g xs) = f (g x) : fmap (f . g) xs
instance Functor Maybe where fmap :: (a -> b) -> Maybe a -> Maybe b fmap _ Nothing = Nothing fmap g (Just a) = Just (g a) -- check the first law for each part: fmap id Nothing = Nothing fmap id (Just a) = Just (id a) = Just a -- check the second law for each part: fmap (f . g) Nothing = Nothing fmap (f . g) (Just x) = Just ((f . g) x) = Just (f (g x)) fmap f (fmap g (Just x)) = Just (f (g x)) = Just ((f . g) x)
Applicative
Laws
-
The identity law:
pure id <*> v = v
-
Homomorphism:
pure f <*> pure x = pure (f x)
Intuitively, applying a non-effectful function to a non-effectful argument in an effectful context is the same as just applying the function to the argument and then injecting the result into the context with pure.
-
Interchange:
u <*> pure y = pure ($ y) <*> u
Intuitively, this says that when evaluating the application of an effectful function to a pure argument, the order in which we evaluate the function and its argument doesn't matter.
-
Composition:
u <*> (v <*> w) = pure (.) <*> u <*> v <*> w
This one is the trickiest law to gain intuition for. In some sense it is expressing a sort of associativity property of (
<*>
). The reader may wish to simply convince themselves that this law is type-correct.
Exercises
(Tricky) One might imagine a variant of the interchange law that says something about applying a pure function to an effectful argument. Using the above laws, prove that
pure f <*> x = pure (flip ($)) <*> x <*> pure f
Solution:
pure (flip ($)) <*> x <*> pure f
= (pure (flip ($)) <*> x) <*> pure f -- <*> is left-associative
= pure ($ f) <*> (pure (flip ($)) <*> x) -- interchange
= pure (.) <*> pure ($ f) <*> pure (flip ($)) <*> x -- composition
= pure (($ f) . (flip ($))) <*> x -- homomorphism
= pure ((flip ($) f) . (flip ($))) <*> x -- identical
= pure f <*> x
Explanation of the last transformation:
flip ($)
has type a -> (a -> c) -> c
, intuitively, it first takes an argument of type a
, then a function that accepts that argument, and in the end it calls the function with the first argument. So (flip ($) 5)
takes as argument a function which gets called with 5
as it's argument. If we pass (+ 2)
to (flip ($) 5)
, we get (flip ($) 5) (+2)
which is equivalent to the expression (+2) $ 5
, evaluating to 7
.
flip ($) f
is equivalent to \x -> x $ f
, that means, it takes as input a function and calls it with the function f
as argument.
The composition of these functions works like this: First flip ($)
takes x
as it's first argument, and returns a function (flip ($) x)
, this function is awaiting a function as it's last argument, which will be called with x
as it's argument. Now this function (flip ($) x)
is passed to flip ($) f
, or to write it's equivalent (\x -> x $ f) (flip ($) x)
, this results in the expression (flip ($) x) f
, which is equivalent to f $ x
.
You can check the type of (flip ($) f) . (flip ($))
is something like this (depending on your function f
):
λ: let f = sqrt
λ: :t (flip ($) f) . (flip ($))
(flip ($) f) . (flip ($)) :: Floating c => c -> c
Also see this question on Stack Overflow which includes alternative proofs.